"I love my sister, but sometimes I don't": A qualitative study into the experiences of siblings of a child with profound intellectual and multiple disabilities†. Issue 4 (1st October 2016) - Luijkx, Jorien; van der Putten, Annette A. J.; Vlaskamp, Carla
ABSTRACT: Background Many previous family quality of life studies have relied on parental information for understanding if and how having a sibling with profound intellectual and multiple disabilities (PIMD) influences the sibling's quality of life. In the current study, children had the opportunity to describe both positive and negative aspects of having a sibling with PIMD. Method Photo elicitation interviews were conducted with 18 children (6–13 years old) and thematically analysed using the following domains: joint activities, mutual understanding, private time, acceptance, forbearance, trust in wellbeing, exchanging experiences, social support, and dealing with the outside world. Results Overall, the children described both positive and negative experiences, indicating that having a sibling with PIMD influenced their quality of life in multiple ways. Most mentioned were experiences classified in the joint activities domain. Conclusion Having a sibling with PIMD influences the life of the interviewed children both positively and negatively. Both the opportunity for shared activities with the sibling with PIMD and moments of private time are important for sibling quality of life.